Modular Joint Using 3D Printer for Compact House in Klang Valley Area - Sidek, Ahmad Anwar Safwan; Wan Ikeramzamani, Wan Farah Nur Iwani (Research in Management of Technology and Business, 2023)
The use of 3D printing technology has brought about new opportunities in designing andproducing furniture. This research concentrates on creating modular furniture joints through 3Dprinting, with the aim of making assembly easier, reducing manufacturing time, and improvingstructural strength. The study explores appropriate materials for printing modular joints, along withdesign principles and methods for constructing joints that are both functional and adaptable. A comprehensive survey is conducted to gather information on user requirements and preferences. The results indicate that plastic materials are the preferred choice, with a focus on long-lasting durability, ease of production, and sustainability. The research aims to identify key design features, develop modular joints using 3D printing, and produce a prototype. This study is important as it contributes to our knowledge of jointing methods, additive manufacturing, and modular design principles. The results will establish guidelines and recommendations for integrating 3D printing into furniture production,benefiting manufacturers and consumers alike. Ultimately, the goal is to produce a durable and versatilemodular junction for furniture that meets the specific preferences and requirements of users. The report confidently examines the promising market for products that incorporate modular joint designs and provide exceptional customer satisfaction. The study is being conducted in the Klang Valley region, with a keen focus on the area’s unique environmental considerations and the specific requirements of its inhabitants.